Contextual factors influencing the roles of patent medicine vendors in the provision of injectable contraception services in Nigeria (2023)
Background Patent medicine vendors (PMVs) play vital roles in the delivery of family planning services in Nigeria and other developing countries. There is a growing recognition of the need to integrate them into the formal health care system as a strategy to increase the contraceptive prevalence rate and achieve universal health coverage.Though promising, the success of this proposition is largely dependent on a critical analysis of the factors which influence their operations. This study was designed to identify the contextual factors influencing the provision of injectable contraceptive services by PMVs and the broader effects of their activities on the health system to inform similar interventions in Nigeria. Methods This was a qualitative study guided by the UK Medical Research Council’s Framework for Complex Interventions. Twenty-seven in-depth interviews were conducted among officials of the association of PMVs, health workers, government regulatory officers and programme implementers who participated in a phased 3-year (2015–2018) intervention designed to enhance the capacity of PMVs to deliver injectable contraceptive services. The data were transcribed and analyzed thematically using NVIVO software. Results The contextual factors which had implications on the roles of PMVs were socio-cultural and religious, the failing Nigerian health system coupled with government regulatory policies. Other factors were interprofessional tensions and rivalry between the PMVs and some categories of health care workers and increasing donors’ interest in exploring the potentials of PMVs for expanded healthcare service provision. According to the respondents, the PMVs bridged the Nigerian health system service delivery gaps serving as the first point of contact for injectable contraceptive services and this increased contraceptive uptake in the study sites. A negative effect of their operation is the tendency to exceed their service provision limits, which has spurred a planned tiered PMV accreditation system. Conclusions This study has highlighted the contextual factors which define the roles and scope of practice of PMVs involved in injectable contraceptive service provision. Strategies and interventions aimed at expanding the healthcare delivery roles of PMVs must be encompassing to address the broader contextual factors which underpin their capacities and functions.